Primary spontaneous pneumothorax during pregnancy - Torres-Cepeda, Duly (2022)
Primary spontaneous pneumothorax is an extremely rare condition duringpregnancy and can occur at any time. Rupture of an apical ampulla or subpleuralbulla is the most common cause in young pregnant women. It is thought to bedue to increased inspiratory activity associated with the peripartum period. Earlydetection and prompt diagnosis of this condition are important for the preventionof some serious complications. The therapeutic methods used in pregnancy do notdiffer essentially from those used in non-pregnant patients. Ambulatory drainage ofthe thorax has been recommended in treatment. Delivery in these women can beperformed vaginally, with a second phase of labor without effort. We present a caseof primary spontaneous pneumothorax that occurred at 35 weeks of gestation in ahealthy 34-year-old primigravida. Its onset was described as pleuritic chest pain anddyspnea of sudden onset. The diagnosis was made by plain chest radiography. Thepatient was successfully treated with chest tube placement